Comparison of coagulation and cutting sphincterotomies with respect to clinical complications - Muhsin KAYA; Selim KARAYALÇIN; Hasan ÖZKAN; Kadir BAHAR; Cihan YURDAYDIN; Necati ÖRMECİ and Abdulkadir DÖKMECİ (Turkish Journal of Gastroenterology, 2019)
-